COMPOSITION OF BOTTOM TRAP IN ARCHIPELAGO FISHING PORT SUNGAILIAT BANGKA DISTRICT BANGKA BELITUNG PROVINCE - Goklas Irmayanti Simbolon; Pareng Rengi; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research was conducted in August-September 2019 at the Sungailiat Archipelago Fisheries Port, aiming to determine differences in the number of the composition of weight and type of catches, using survey methods. Based on the types of species caught, Leopard Coralgrouper (Plectropomus leopardus) 91 tails (271,5 kg), Aerolate grouper (Epinephelus fuscoguttatus) 693 tails (231,9 kg), Spotted grouper (Epinephelus tauvina) 42 tails (205,1 kg), Brownstripe snapper(Lutjanus Vitta) 3166 tails (457,8) Yellowtails fusilier (Caesio cuning) 4536 tails (752.8 kg), Orange sponted spinefoot (Siganus Guttatus) 1022 tails (145,8 kg), Starry trigerfish (Abalistes Stellaris) 1110 tails (370, 6 kg), Ketarap (Balistoides viridescens) 222 tails (220,5 kg), Crimson snapper (Lutjanus Sp) 76 tails (221,5 kg), Sweetlips (Plectorhinchus spp) 860 tails (216.2 kg), Tiletrevally (carrax)melampygus) 335 tails (69 kg), Blackfin crevalle (Alepes melanopera) 93 tails (31 kg), and Emperors (Lethrinus lentjan) 100 tails (50,3 kg).Soakingbubu five-day gain the most catches by weight during the study. The result of t-test concludes the five day and seven day catch both by the number of fish and the weight of the caught fish is significantly different.Keywords :Bottom trap, composition of catc,PPN Sungailiat Bangka Regency